THE PRODUCTION PLAN IS THE MAIN FACTOR IN THE FUNCTIONING OF THE ENTERPRISE - G.T. Shamshimetova; D.Mirkamalov; G.G. Bazarbayeva (Journal Park Publishing, 2023)
This article is about the formation of a production plan in garment enterprises. The production plan is the most difficult part of the system of operational and long–term plans, since it covers almost all factors of the functioning of the enterprise. If the planning was carried out without taking into account all possible negative conditions and force majeure, then all other components of a comprehensive business plan become meaningless.
Keywords: assortment of sewing products, planning, assortment formation, rational assortment, assortment stability, assortment structure.